USE OF NON-TRADITIONAL FORMS IN THE CONTEXT OF THE EDUCATIONAL PROCESS OF JUNIOR SCHOOLCHILDREN - Shpachuk, L.R. (Pedagogy of Higher and Secondary Education, 2010)
In this article the forms of junior pupils’ instruction , which are alternative to traditional, providing not only all-round and optimum development but also pupils’ upbringing are considered.